CAPACITY ANALYSIS OF AIRPORT PASSENGER TERMINAL: TERMINAL 2 SOEKARNO CASE STUDY -HATTA INTERNATIONAL AIRPORT - , IRFAN N PRATAMA; , Ir. Dewanti, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Passenger movement in Soekarno Hatta International Airport has reached 59.7 million passengers in 2013, ranks it as the 10th busiest airport in the world by passenger traffic (ACI, 2014). This very huge number of passenger traffic far exceeds Soekarno-Hatta International Airportâs existing capacity, which could only accommodate approximately 22 million passengers per annum. Consequently, one of the main problems arises from this condition is high density problem in passenger terminals of Soekarno-Hatta International Airport. This research aims to analyze and assess current condition of Terminal 2 of Soekarno Hatta International Airport. The analyses and calculations were done in three ways